Orientation of educational-educator process of school on maintenance and strengthening of health of students: polish experience - Larysa Slyvka (Vasyl Stefanyk Precarpathian National University, 2017)
Content bases of healthsaving education of junior schoolchildren of Poland are analyzedin the article: educational and prophylactic programs, projects on strengthening health ofjunior schoolchildren. The task of school is the healthsaving education sent to forming a habitto care of the health and health of other people, and also on creation of favorable terms for ahealth. In Polish schools on all stages of educating strengthening of health comes true bymeans of physical education, biology, natural science (environment), domestic education andintersubject connections. Polish schools work on such educational and prophylacticprograms, as: prophylactic program of fight against AIDS and HIV-infections, "Clean airround us", "My child goes to school", "Glass of milk", "Hold a form", "Fruit at school","Healthy feed and physical activity in schools", "Does not smoke to me, please". Key words: healthsaving education, junior schoolchildren, initial school, educationaland prophylactic programs.